THE LOCAL CONTENT ANALYSIS OF JAVANESE MATERIAL FOR FIFTH GRADERS OF ELEMENTARY SCHOOL - Wisda Amalia Putri; Sony Irianto; Cicih Wiarsih (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2014)
The aim of this research was to analyze the local content of Javanese language material for fifth graders elementary school by using formative scoring sheet for mterial which were used by teacher of fifth graders of elementary school in North Purwokertp district was Remen Basa Jawi 5. This research was qualitative research with content analysis technique.the data cllection technique was documentary which gotten from Remen Basa Jawi 5 book. The data was analyzed by using compatible result, less compatible, and not compatible. The data presentation was description by using narration. Based on the analysis result, the content appropriateness of Remen Basa Jawi 5 was less compatible with competency standard and basic competence, students’ need, and the reading criterioan, clarity f information, and the conformity of Javanese language theorm. The presentation’s result was less compatible in presentation organization’s criteria, motivation’s giving, and the completeness of information. The result of graphic analysis was less compatible in using font aspect,illustration, and performance design